Enrichment of Phosphatidylinositol 4, 5-Bisphosphate in the Extra-Invasive Hyphal Membrane Promotes Colletotrichum Infection of Arabidopsis thaliana. (15th April 2019) - Shimada, Takashi L; Betsuyaku, Shigeyuki; Inada, Noriko; Ebine, Kazuo; Fujimoto, Masaru; Uemura, Tomohiro; Takano, Yoshitaka; Fukuda, Hiroo; Nakano, Akihiko; Ueda, Takashi
Abstract: Pathogenic fungi from the genus Colletotrichum form invasive hyphae; the hyphae are surrounded by an extra-invasive hyphal membrane (EIHM), which is continuous with the plant plasma membrane. Although the EIHM plays a crucial role as the interface between plant and fungal cells, its precise function during Colletotrichum infection remains elusive. Here, we show that enrichment of phosphoinositides (PIs) has a crucial role in Colletotrichum infection. We observed the localization of PIs in Arabidopsis thaliana cells infected by A. thaliana -adapted Colletotrichum higginsianum ( Ch ), and found that phosphatidylinositol 4, 5-bisphosphate [PI(4, 5)P2 ] was extremely enriched in the EIHM during Ch infection. We also found that phosphatidylinositol 4-phosphate-5 kinase (PIP5K), which catalyzes production of PI(4, 5)P2, also accumulated at the EIHM. The overexpression of PIP5K3 in A. thaliana increased hyphal invasion by Ch . An exocytic factor, EXO84b, was targeted to the EIHM during Ch infection, although endocytic factors such as CLATHRIN LIGHT CHAIN 2 and FLOTILLIN 1 did not. Intriguingly, the interfacial membranes between A. thaliana and powdery mildew- or downy mildew-causing pathogens did not accumulate PI(4, 5)P2 . These results suggest that Ch could modify the PI(4, 5)P2 levels in the EIHM to increase the exocytic membrane/protein supply of the EIHM for successful infection. Our results also suggest that PI(4, 5)P2 biosynthesis is a promising target for improved defense against Colletotrichum infection.